2017: роман / Ольга Славникова - Славникова Ольга Александровна (Вагриус, 2008)
Экземпляры: К/Х (20220802) / Инвентарный номер: 42200 / Цена: 162.03 / Сис.шифр: Ш6(2=Р)7 / Авт.знак: С 47 / ГРНТИ: 17.82.31 / ББК: Ш6(2=Р)7